A prospective comparison of cold snare polypectomy using traditional or dedicated cold snares for the resection of small sessile colorectal polyps - Dwyer, Jeremy P.; Tan, Jonathan Y. C.; Urquhart, Paul; Secomb, Robyn; Bunn, Catherine; Reynolds, John; La Nauze, Richard; Kemp, William; Roberts, Stuart; Brown, Gregor (Endoscopy International Open, 2017)
Background and study aims The evidence for efficacy and safety of cold snare polypectomy is limited. The aim of this study was to assess the completeness of resection and safety of cold snare polypectomy, using either traditional or dedicated cold snares.Patients and methods This was a prospective, non-randomized study performed at a single tertiary hospital. Adult patients with at least one colorectal polyp (size ≤ 10 mm) removed by cold snare were included. In the first phase, all patients had polyps removed by traditional snare without diathermy. In the second phase, all patients had polyps removed by dedicated cold snare. Complete endoscopic resection was determined from histological examination of quadrantic polypectomy margin biopsies. Immediate or delayed bleeding within 2 weeks was recorded.Results In total, 181 patients with 299 eligible polyps (n = 93 (173 polyps) traditional snare group, n = 88 (126 polyps) dedicated cold snare group) were included. Patient demographics and procedure indications were similar between groups. Mean polyp size was 6 mm in both groups (P = 0.25). Complete polyp resection was 165 /173 (95.4 %; 95 %CI 90.5 – 97.6 %) in the traditional snare group and 124/126 (98.4 %; 95 %CI 93.7 – 99.6 %) in the dedicated cold snare group (P = 0.16). Serrated polyps, compared with adenomatous polyps, had a higher rate of incomplete resection (7 % vs. 2 %, P = 0.03). There was no statistically significant difference in the rate of immediate bleeding (3 % vs. 1 %, P = 0.41) and there were no delayed hemorrhages or perforations.Conclusions Cold snare polypectomy is effective and safe for the complete endoscopic resection of small (≤ 10 mm) colorectal polyps with either traditional or dedicated cold snares.